2016
DOI: 10.1142/s0219649216500155
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Influencing Knowledge Sharing in Student–Supervisor Relationship: A Structural Equation Modelling Analysis

Abstract: Although knowledge sharing (KS) and personality traits are primarily studied in business organisations, these issues are equally important for universities. However, few attempts have been made to investigate the relationship between personality traits and KS, particularly in the context of Malaysian higher education. The present study¯lls the research gap by examining the e®ects of personality traits -speci¯cally agreeableness, conscientiousness and openness to experienceon KS in the student-supervisor relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
2
13
0
1
Order By: Relevance
“…Conscientiousness people are more likely to socialise in the organisation; these characteristics are vital in the process of KS. In recent research, Memon et al (2016) found a positive association between KS and conscientiousness. Hence, by characteristics possessed by the conscientiousness people and the results of prior studies (Matzler et al, 2008;Memon et al, 2016), we conjecture the fourth research hypothesis as follows: H4.…”
Section: Neuroticismmentioning
confidence: 92%
See 3 more Smart Citations
“…Conscientiousness people are more likely to socialise in the organisation; these characteristics are vital in the process of KS. In recent research, Memon et al (2016) found a positive association between KS and conscientiousness. Hence, by characteristics possessed by the conscientiousness people and the results of prior studies (Matzler et al, 2008;Memon et al, 2016), we conjecture the fourth research hypothesis as follows: H4.…”
Section: Neuroticismmentioning
confidence: 92%
“…In recent research, Memon et al (2016) found a positive association between KS and conscientiousness. Hence, by characteristics possessed by the conscientiousness people and the results of prior studies (Matzler et al, 2008;Memon et al, 2016), we conjecture the fourth research hypothesis as follows: H4. Conscientiousness is positively linked to KS.…”
Section: Neuroticismmentioning
confidence: 92%
See 2 more Smart Citations
“…Over the last decades, many studies have focused on employee turnover (Callea et al, 2016;Han et al, 2016;Memon et al, 2016b;Ahmed et al, 2015;Rabbi et al, 2015). This reflects the significance of turnover, and how many organizations perceive turnover negatively, as stipulated by Lee et al (2010).…”
Section: Introductionmentioning
confidence: 99%